Direção de atores no cinema brasileiro realizado no Rio Grande do Sul - Vargas, Gilson Padilha de (2012)
The present text shows the theme of actors direction in cinema, with two parameters: the temporal framing, localizing the subject after the Return of Brazilian Cinema (Retomada do Cinema Brasileiro), until the actual moment, and the regional framing, prioritizing and focusing the complexity of the theme on the state of Rio Grande do Sul (Brazil). For that, five of the most actives brazilian directors based on Rio Grande do Sul have been interviewed. We also research support of theory in authors like Jean-Jacques Roubine, Richard Boleslavski and in Constantin Stanislavsky. The work begins with a brief introduction, explaining the sparks who motivate the incursion in the present theme; then, the work makes a approximation about the relation between director and actor in the cinema and also presents an approach about the pragmatic actions during the process of directing actors. It also approach the regional framing, at the directors and space of work chapter and finishes with some brief considerations.